Lyndon B. Johnson - Gunderson, Megan M., 1981- (2017)
"This biography introduces readers to the life of Lyndon B. Johnson including his military service, early political career, and key events from Johnson's administration including the Civil Rights Act, the Vietnam War, and the Voting Rights Act. Information about his childhood, family, personal life, and retirement years is included. A timeline, fast facts, and sidebars provide additional information."--Publisher's website.
Lyndon B. Johnson -- Timeline -- Growing up -- School and family -- Young politician -- Vice President -- President Johnson -- Civil rights -- After politics -- Office of the President -- Presidents and their terms.
Includes index.
"The 36th President of the United States"--Cover.
Keywords: Johnson, Lyndon B. -- 1908-1973 -- Juvenile literature; Johnson, Lyndon B. -- 1908-1973.; Johnson, Lyndon B. -- 1908-1973.; Presidents -- United States -- Biography -- Juvenile literature; Presidents -- United States -- Biography; Presidents -- United States -- Biography -- Juvenile literature; Presidents; United States; Biography; Juvenile works